Studi Komparasi Ratu Ayu Mas Manik Meketel Di Pura Luhur Pucak Penataran Dengan Deva Dalam Veda - Ni Luh Putu Yuliani Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The localization of Hinduism is not only happening in Bali but also in other regions outside Bali. So that often various names of deva or bhatara are found in each temple or other holy place in Bali which is certainly different from the name deva in the Vedas. Surely it is necessary to reconnect these local appellations (manifestations) of God with the name deva in Veda, by looking for its similarity with deva in the Vedas. It is hoped that the boundary of the argument does not stop at the statement that 'the various namings or designations of God (bhatara) known especially in Bali are names that have undergone localization (local theology)' without being reconnected with the deva in the Vedas tag. Therefore, devotees will understand that Veda and Hinduism are really able to adapt and be localized to local traditions. It also aims to lead to an increase in people's understanding from local theology to Vedic theology (Brahmawidya). The research method used is a qualitative descriptive research method that seeks to uncover the relationship of similarities between prabhawa/manifestations of God named locally and the names of deva in the Vedas. Ratu Ayu Mas Manik Meketel, who is one of the manifestations of God in the local theological concept, also has a similar relationship with deva-deva in the Vedic theological concept, namely Devi Laksmi and Deva Visnu.